Self-repairing composite material for new energy vehicle tire, preparation method of self-repairing composite material and tire
By adopting a double-layer self-repair composite material design in new energy vehicle tires, combined with dynamic vulcanized rubber system and thermal fillers, the problem of dropping air pressure and weakening of self-repair effect in high load and high temperature environments is solved, and rapid repair and durability are achieved.
Patent Information
- Application Number
- CN202411716740.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-27
AI Technical Summary
New energy vehicle tires are prone to rapid drop in air pressure, weakening of self-repair effect or loss of repair ability under high load and high temperature environments, especially when the repair effect is poor when the impact of irregular piercings or complex-shaped firmware.
Designed with a double-layer self-repair composite material, the first layer quickly responds to small punctures and slight cracks through dynamic vulcanized rubber systems and thermally conductive fillers, and conducts heat and dissipates heat. The second layer provides strong repair support through thermoplastic polyurethane elastomers, repaired microcapsules and modified polyimide fibers, with high strength and long-lasting fatigue resistance.
It realizes rapid repair of tire damage under complex road conditions, has good durability and high temperature stability, effectively protects the safety of drivers and passengers, and extends the service life of the tires.
Smart Images

Figure BDA0005157043860000181
Abstract
Description
Technical Field
[0001] The present application relates to a self-repairing composite material for new energy vehicle tires, a preparation method thereof, and a tire, and belongs to the field of tire materials. Background Art
[0002] With the development of new energy vehicles, electric vehicles and hybrid vehicles have gradually become mainstream, and the market has higher and higher requirements for their range, power performance and safety. As an important part of the vehicle, tires not only bear the main function of the vehicle's contact with the ground, but also directly affect driving safety and comfort. During the driving process of the car, the rapid drop in air pressure caused by a puncture poses a threat to the personal safety of passengers and the stability of the vehicle.
[0003] At present, some sealing and repair adhesive products have been developed in the existing technology. For example, in Chinese patent application CN114058293A - a self-repairing tire sealant and its preparation method and self-repairing tire, butyl rubber is used as the core and reinforcing fillers and other substances are added to prepare the self-repairing sealant, which can avoid rapid gas leakage to a certain extent. But in fact, the self-adhesion of butyl rubber is poor, and the glue may delaminate in a short period of time. In Chinese patent application CN116396605A - a disc-type self-repairing sealing material for new energy vehicle tires to prevent punctures and its preparation method, it is proposed to use modified polyurethane sealing materials and active fillers to improve durability to a certain extent.
[0004] However, in the actual application of new energy vehicle tires, there will be complex performance requirements. New energy vehicles, especially electric vehicles, have a higher torque output, which means that the tires bear a larger load when starting, accelerating, and braking. At the same time, high-speed driving will cause heat accumulation on the inner surface of the tire. Ordinary repair materials have limited impact resistance and high temperature resistance. Long-term driving may age, resulting in a weakening of the self-repair effect or loss of repair ability. High temperature will also accelerate the aging of tire materials, increase cracks, wear and other damage on the tire surface. At the same time, traditional self-repair glues may suffer fatigue damage under the dynamic stress of the tire, resulting in a decrease in the repair effect. In addition, the existing self-repair sealants can repair small punctures (such as fine nails), but the repair effect is poor for small-area irregular damage caused by irregular punctures or complex-shaped firmware (such as multi-directional cracks caused by sharp firmware). The damaged area will still gradually leak air, and it is impossible to form a good repair effect in a short time. Summary of the invention
[0005] In order to solve the above problems, the present application proposes a self-repairing composite material for new energy vehicle tires, a preparation method and a tire. By setting a double-layer self-repairing composite material, the first layer on the outside can quickly respond to small punctures and slight cracks, and can quickly conduct heat and dissipate heat to avoid accumulation of heat areas, and has good high-temperature stability. The second layer on the inside can provide strong repair support, has high strength and long-lasting fatigue resistance, can meet the needs of new energy vehicle tires for rapid repair when damaged under complex road conditions, and has good durability to effectively protect the safety of drivers and passengers.
[0006] According to one aspect of the present application, a self-repairing composite material for a new energy vehicle tire is provided, which is composed of a first self-repairing layer and a second self-repairing layer connected together;
[0007] The first self-repairing layer is prepared by the following ingredients, measured by weight: 80-120 parts of a dynamic vulcanized rubber system, 18-35 parts of a functional filler system, and 3-8 parts of a vulcanization accelerator; the dynamic vulcanized rubber system includes polypropylene, natural rubber, and ethylene-propylene rubber, and the amount of polypropylene added to the dynamic vulcanized rubber system does not exceed 30%; the functional filler system includes a thermally conductive filler, and the thermally conductive filler includes modified boron nitride and aluminum oxide; the vulcanization accelerator includes sulfur and N-cyclohexyl-2-benzothiazole sulfenamide;
[0008] The second self-repairing layer is prepared by the following ingredients, measured by weight: 100-110 parts of thermoplastic polyurethane elastomer, 30-40 parts of repair microcapsules and 10-15 parts of modified polyimide fibers; the repair microcapsules are composed of a core material and a capsule wall, and the core material is an epoxy resin mixture or a curing agent mixture.
[0009] The dynamic vulcanized rubber system is composed of resin phase polypropylene (PP) and rubber phase (natural rubber NR + ethylene propylene rubber EPDM). First, PP acts as a continuous phase to support and enhance the rubber phase, while the rubber phase provides flexibility and toughness. The two form a micro-dispersed structure through dynamic vulcanization, which can comprehensively improve the heat resistance, toughness and durability of the composite material.
[0010] Furthermore, the rubber phase adopts a combination of NR+EPDM. With the help of the high elasticity, low-temperature flexibility and good tear resistance of natural rubber NR, it helps to absorb impact and suppress cracks under dynamic loads. Combined with ethylene propylene rubber (EPDM), it gives the material stability in high temperature environments and improves compatibility with functional fillers and matrix.
[0011] By limiting the addition amount of polypropylene to no more than 30%, it is ensured that the material has sufficient flexibility and resistance to crack propagation, while maintaining a certain rigidity and heat resistance, so that the material can adapt to the dynamic load environment of the tire.
[0012] Optionally, the weight ratio of natural rubber to EPDM in the dynamically vulcanized rubber system is (2-3): 1. Specifically, by limiting the weight ratio of the two, it can ensure that the PP and rubber phases form a stable interface structure, better adapt to high temperature and high torque environments, and provide excellent impact absorption capabilities.
[0013] Optionally, the weight ratio of modified boron nitride and aluminum oxide in the thermally conductive filler is (2-3):1;
[0014] The modified boron nitride comprises silane-modified boron nitride and polymer-coated modified boron nitride, and the weight ratio is (1.5-2):1.
[0015] Specifically, the preparation method of silane-modified boron nitride is to dissolve silane coupling agent KH550 in ethanol solution (concentration 95%), stir evenly, add boron nitride, react at 80° C. for 2 hours; filter, wash and dry to obtain silane-modified boron nitride.
[0016] The preparation method of polymer-coated modified boron nitride is to disperse boron nitride in solvent toluene, stir evenly, add monomer acrylate and initiator (ammonium persulfate), and carry out polymerization reaction at 60°C; after the reaction is completed, filter, wash and dry the product to form modified boron nitride with a surface coated with a polymer.
[0017] Specifically, the particle size of the modified boron nitride is 8-10 μm, and the particle size of the aluminum oxide is 1-3 μm.
[0018] By using modified boron nitride and alumina as thermal conductive fillers, material aging, performance degradation or damage caused by long-term high temperature accumulation can be avoided, and the high temperature environment of high torque and long-term operation of new energy vehicles can be adapted. By using modified boron nitride, the interface bonding strength between it and the matrix material is improved, the dispersion of the filler in the matrix is improved, and the interruption of the heat conduction path is avoided, thereby enhancing the overall thermal conductivity of the material. Alumina has a certain interface compatibility with the rubber matrix. The compounding of alumina and modified boron nitride can optimize thermal conductivity and improve mechanical properties through the synergy of fillers with different particle sizes and morphologies.
[0019] The purpose of using two types of modified boron nitride is to optimize its compatibility and dispersibility with the matrix at different levels: the surface of silane-modified boron nitride introduces active groups to enhance the interfacial bonding force with the matrix material (especially the rubber matrix), improve the chemical compatibility between the filler and the rubber phase, reduce the thermal resistance between the interfaces, and prevent the filler from agglomerating to ensure uniform dispersion in the matrix. Polymer-modified boron nitride can enhance its wettability and physical adsorption in the rubber matrix, improve the durability of the filler, prevent it from falling off or precipitating under high temperature and dynamic stress conditions, and reduce the possible damage of the filler to the matrix material, while avoiding adverse effects on the vulcanization process of the rubber phase. In general, silane modification enhances chemical bonding, and polymer coating provides physical reinforcement. The combination of the two effectively optimizes the thermal conductivity and mechanical properties of boron nitride in the rubber matrix.
[0020] Optionally, the functional filler system further comprises a crack suppression filler and a dynamic enhancement filler;
[0021] The weight ratio of the thermal conductive filler, crack suppression filler and dynamic reinforcement filler is (6-12): (3-7): (2-5) respectively.
[0022] Preferably, the crack suppression filler is silane-modified nano-silicon powder, and the dynamic enhancement filler is nano-cerium oxide.
[0023] The particle size of nano cerium oxide is 20-50nm, and the particle size of nano silicon powder is 10-50nm.
[0024] The preparation method of silane-modified nano-silicon powder is as follows:
[0025] a1. Cleaning of nano-silicon powder: Ultrasonic dispersion of nano-silicon powder in deionized water for 30 minutes, clean impurities and particles that may be attached to the surface, filter, and dry with hot air at 60°C to constant weight;
[0026] a2. Add silane coupling agent KH550 to anhydrous ethanol at a volume ratio of coupling agent: solvent = 1:10, and stir evenly; add a small amount of deionized water (silane hydrolysis ratio is silane: water = 1:3, molar ratio), stir until completely dissolved, and then adjust the solution pH to 4 (using glacial acetic acid) to promote silane hydrolysis to form active groups.
[0027] a3. Add the dried nano-silicon powder to the silane solution and stir evenly; ultrasonically treat for 30 minutes to ensure that the powder is evenly dispersed and prevent agglomeration; place the mixed solution in a water bath at 80°C for 2 hours, and filter and dry to obtain the result.
[0028] By adding crack suppression fillers and dynamic reinforcement fillers to the thermal conductive filler system, silane-modified nano-silicon powder can effectively passivate crack tips, thereby delaying crack propagation; at the same time, under dynamic load, cerium oxide particles can help disperse periodic stress in the material to prevent stress concentration from causing local material damage. Through weak interaction with rubber segments, cerium oxide particles can also fill and stabilize microscopic damage areas and slow down the rate of fatigue accumulation. The reasonable combination and synergy of the two can effectively enhance the dynamic fatigue performance and crack propagation resistance of composite materials while improving thermal conductivity, thereby meeting the strict requirements of new energy vehicle tires in high-load and high-frequency use environments.
[0029] Optionally, the weight ratio of sulfur to N-cyclohexyl-2-benzothiazolesulfenamide in the vulcanization accelerator is (1-1.5):1.
[0030] Optionally, the method for preparing the first self-repairing layer comprises the following steps:
[0031] S1: Add polypropylene, natural rubber and EPDM into an internal mixer at a temperature of 155-165°C and mix for 5-10 minutes;
[0032] S2: Add the vulcanization accelerator, raise the temperature to 170-180°C, dynamically mix for 3-5 minutes, and then add the functional filler system;
[0033] S3: After continuing to mix for 2-4 minutes, the first self-repairing layer is obtained by pressing and molding through an open mixer;
[0034] Preferably, the pressure of the open rolling molding in step S3 is 10-12 MPa, the temperature is 160-165° C., and the time is 8-10 min.
[0035] Specifically, in steps S1 and S2, the rotation speed is 30 rpm, and the thickness of the first self-repairing layer is 1-2 mm, preferably 1.5 mm.
[0036] Optionally, the repair microcapsules include type A microcapsules and type B microcapsules in a weight ratio of (1.2-1.4):1;
[0037] The type A microcapsule is an epoxy resin microcapsule, the core material is DGEBA epoxy resin and dibutyl hydroxytoluene, the weight ratio is (60-70):1, and the capsule wall is polymethyl methacrylate;
[0038] The B-type microcapsule is a curing agent microcapsule, the core material is tetraethylenepentamine and dibutylhydroxytoluene, the weight ratio is (55-65):1, and the capsule wall is polyurea.
[0039] Specifically, the particle sizes of type A microcapsules and type B microcapsules are both 100 μm.
[0040] 1. The preparation method of type A microcapsules is:
[0041] a. Preparation of aqueous phase:
[0042] Add distilled water and 3% PVA dispersant into a three-necked flask and stir evenly to form a stable water phase.
[0043] b. Preparation of core material mixture:
[0044] DGEBA epoxy resin and butylated hydroxytoluene were mixed according to a weight ratio and heated to 40° C. to make them completely miscible.
[0045] c. Emulsified core material:
[0046] The core material mixture was slowly added dropwise to the aqueous phase while stirring at a high speed of 1500 rpm to form a stable emulsion.
[0047] d. Polymerization of capsule wall:
[0048] Methyl methacrylate (MMA, capsule wall monomer) and a small amount of AIBN (initiator) were added to the emulsion, and the mixture was stirred and heated to 75° C. to carry out free radical polymerization for 3 h.
[0049] e. Cooling and post-processing:
[0050] After the reaction was completed, the mixture was cooled to room temperature (25°C), the microcapsules were filtered out, washed with distilled water for several times, and finally dried at 40°C to obtain epoxy resin microcapsules.
[0051] 2. The preparation method of type B microcapsules is:
[0052] a. Preparation of aqueous phase:
[0053] Add distilled water and 3% PVA dispersant into a three-necked flask and stir evenly to form a stable water phase.
[0054] b. Preparation of core material mixture:
[0055] Tetraethylenepentamine and butylated hydroxytoluene were mixed according to a weight ratio.
[0056] c. Emulsified core material:
[0057] The core material mixture was slowly added dropwise to the aqueous phase while stirring at a high speed of 1500 rpm to form a stable emulsion.
[0058] d. Polymerization of capsule wall:
[0059] Isocyanate monomer (HDI) and PEG were added to the emulsion in proportion, and an organic amine catalyst (triethylamine) was added dropwise. The temperature was controlled at 65°C, and an interfacial polymerization reaction was carried out under stirring to generate a polyurea capsule wall. The reaction time was 2 hours.
[0060] e. Cooling and post-processing:
[0061] After the reaction was completed, the mixture was cooled to room temperature (25°C), the microcapsules were filtered out, washed with distilled water for several times, and finally dried at 40°C to obtain curing agent microcapsules.
[0062] By using thermoplastic polyurethane elastomer, repair microcapsules and modified polyimide fibers, and limiting the proportion of each component, the three components work together in the composite material. The repair microcapsules can rupture when violently impacted by external sharp objects and quickly fill cracks and gaps. On the one hand, the TPU matrix can quickly fill cracks and gaps at the rupture under dynamic load, buying time for the flow filling and curing of the broken epoxy resin of the microcapsules. On the other hand, its excellent interfacial bonding properties work synergistically with the modified polyimide fibers to provide a stable composite matrix, and fiber reinforcement prevents the generation or extension of secondary cracks.
[0063] Optionally, the method for preparing the second self-repairing layer comprises the following steps:
[0064] S1: Add thermoplastic polyurethane elastomer into a mixer at a temperature of 110-130°C and mix for 5-8 minutes;
[0065] S2: Add the repair microcapsules and modified polyimide fibers evenly into the mixer, control the temperature at 100-120°C, and mix for 20-30 minutes;
[0066] S3: sending the uniformly mixed material into an extruder for extrusion molding, and obtaining the second self-repairing layer after cooling and molding;
[0067] Preferably, the extrusion molding parameters in step S3 are a temperature of 160-180° C. and a pressure of 6-8 MPa.
[0068] Specifically, the preparation method of the modified polyimide fiber (average diameter 5-10 μm, length 3-6 mm) is as follows: repeatedly rinse the polyimide fiber with deionized water until it is neutral, filter and dry it for later use; add deionized water to 50 mL of ethanol and mix them in a volume ratio of (95:5); add silane coupling agent KH550 (mass concentration is 2%), and stir evenly with a magnetic stirrer; adjust the pH value of the solution to 4.5-5.0 (using dilute hydrochloric acid), and let it stand for 30 minutes to complete the hydrolysis.
[0069] Add polyimide fiber to the above silane coupling agent solution at a ratio of 1g fiber mass to 50mL solution volume; stir and react in a 70℃ constant temperature water bath for 2h, while maintaining slight mechanical stirring to ensure uniform fiber infiltration. After the reaction is completed, take out the fiber and rinse it with ethanol and deionized water several times to remove the unreacted silane coupling agent. Place the fiber in a vacuum drying oven and dry it at 80℃ for 12h to obtain modified polyimide fiber.
[0070] According to another aspect of the present application, a method for preparing the self-repairing composite material for new energy vehicle tires as described above is provided, comprising the following steps:
[0071] (1) grinding the bottom surface of the first self-repairing layer and the top surface of the second self-repairing layer with sandpaper, and then cleaning them with ethanol;
[0072] (2) After being completely dried, the preheated adhesive is coated on the top surface of the second self-repairing layer, and then the first self-repairing layer and the second self-repairing layer are laminated and pressurized. After cooling and curing, the self-repairing composite material for new energy vehicle tires is obtained.
[0073] Specifically, in step (1), 120# sandpaper is used for polishing, and in step (2), the adhesive is preheated to 125° C., and the thickness of the adhesive layer is controlled to be 0.1 mm; the pressure is 0.4 MPa, the temperature is 130° C., and it is maintained for 8 minutes.
[0074] According to another aspect of the present application, a tire is also provided, which includes, from the outside to the inside, a tread layer, a self-repairing composite material layer and a tire inner layer, wherein the self-repairing composite material layer is the self-repairing composite material for new energy vehicle tires as described above or the self-repairing composite material for new energy vehicle tires prepared by the above preparation method, wherein the first self-repairing layer is arranged close to the tread layer, and the second self-repairing layer is arranged close to the tire inner layer.
[0075] The beneficial effects of this application include but are not limited to:
[0076] 1. The self-repairing composite material for new energy vehicle tires provided in the present application realizes dynamic suppression and repair of cracks through the design of a double-layer self-repairing composite material, combined with the advantages of a dynamic vulcanized rubber system and repair microcapsules; wherein, the functional filler system in the first self-repairing layer provides excellent thermal conductivity and crack suppression, and the repair microcapsules in the second self-repairing layer cooperate with TPU to first fill and plug the gaps when cracks occur, and simultaneously and quickly release the core material to complete the colloid solidification, and finally effectively realize self-repair of the damaged parts, and the modified fiber provides stable support, and the overall impact resistance is excellent, which effectively extends the service life of the tire.
[0077] 2. The self-repairing composite material for new energy vehicle tires provided in this application, by introducing a combined thermal conductive filler system of modified boron nitride and aluminum oxide, can quickly dissipate the heat generated by the tire during driving, reduce heat accumulation, and reduce the impact of temperature rise on the performance of the self-repairing material. At the same time, the reasonable proportion of the filler optimizes the mechanical properties of the composite material and improves the overall thermal stability and fatigue resistance.
[0078] 3. The self-repairing composite material for new energy vehicle tires provided in the present application, the addition of modified polyimide fiber in the second self-repairing layer not only significantly enhances the mechanical properties of the material, but also has good interface bonding force, so that the microcapsules are effectively dispersed and have good compatibility with the matrix material, thereby ensuring the reliability of the self-repairing material under cyclic deformation conditions and preventing interlayer delamination and crack propagation. DETAILED DESCRIPTION
[0079] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0080] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0081] The polypropylene, natural rubber and EPDM used in this application are all commercially available materials, wherein the physicochemical parameters of natural rubber are Mooney viscosity (ML (1+4) 100°C): 50-70, tensile strength ≥ 20MPa; Mooney viscosity (ML (1+4) 100°C) of EPDM: 30-60, ethylene content: 50-60wt%, tensile strength ≥ 10MPa. In the following examples, the parameters and preparation methods of various substances that are not detailed are all adopted from the contents recorded in the specification.
[0082] Example 1 Self-repairing composite material 1#
[0083] The self-repairing composite material 1# is composed of a first self-repairing layer and a second self-repairing layer connected together;
[0084] The first self-repairing layer: The first self-repairing layer is prepared by including the following ingredients, measured by weight: 100 parts of a dynamic vulcanized rubber system, 20 parts of a functional filler system and 5 parts of a vulcanization accelerator; the dynamic vulcanized rubber system includes polypropylene, natural rubber and ethylene-propylene rubber, and the amount of polypropylene added to the dynamic vulcanized rubber system is 25%; the functional filler system includes a thermally conductive filler, and the thermally conductive filler includes modified boron nitride and alumina; the vulcanization accelerator includes sulfur and N-cyclohexyl-2-benzothiazole sulfonamide.
[0085] The weight ratio of natural rubber to EPDM in the dynamic vulcanized rubber system is 2.5:1. The weight ratio of modified boron nitride to alumina in the thermal conductive filler is 2:1; the modified boron nitride includes silane-modified boron nitride and polymer-coated modified boron nitride, with a weight ratio of 1.5:1. The weight ratio of sulfur to N-cyclohexyl-2-benzothiazole sulfenamide in the vulcanization accelerator is 1.5:1.
[0086] The preparation method of the first self-repairing layer comprises the following steps:
[0087] S1: Add polypropylene, natural rubber and EPDM into an internal mixer at 160°C and mix for 8 minutes;
[0088] S2: Add the vulcanization accelerator, raise the temperature to 175°C, and add the functional filler system after dynamic mixing for 4 minutes;
[0089] S3: After continuing to mix for 3 minutes, the first self-repairing layer is obtained by pressing and molding through an open mill; the pressure of the open mill molding in step S3 is 11 MPa, the temperature is 165°C, and the time is 9 minutes.
[0090] The second self-repairing layer: The second self-repairing layer is prepared by including the following ingredients by weight: 105 parts of thermoplastic polyurethane elastomer, 30-40 parts of repair microcapsules and 12 parts of modified polyimide fibers; the repair microcapsules are composed of a core material and a capsule wall, and the core material is an epoxy resin mixture or a curing agent mixture.
[0091] The repair microcapsules include Class A microcapsules and Class B microcapsules, with a weight ratio of 1.3:1; Class A microcapsules are epoxy resin microcapsules, the core materials of which are DGEBA epoxy resin and butylated hydroxytoluene, with a weight ratio of 65:1, and the capsule wall is polymethyl methacrylate; Class B microcapsules are curing agent microcapsules, the core materials of which are tetraethylenepentamine and butylated hydroxytoluene, with a weight ratio of 60:1, and the capsule wall is polyurea.
[0092] The preparation method of the second self-repairing layer comprises the following steps:
[0093] S1: Add thermoplastic polyurethane elastomer into a mixer at 120°C and mix for 6 minutes;
[0094] S2: Add the repair microcapsules and modified polyimide fibers evenly into the mixer, control the temperature at 110°C, and mix for 25 minutes;
[0095] S3: sending the uniformly mixed material into an extruder for extrusion molding, and obtaining the second self-repairing layer after cooling and molding; the extrusion molding parameters in step S3 are a temperature of 170° C. and a pressure of 7 MPa.
[0096] The method for preparing the self-repairing composite material 1# comprises the following steps:
[0097] (1) grinding the bottom surface of the first self-repairing layer and the top surface of the second self-repairing layer with sandpaper, and then cleaning them with ethanol;
[0098] (2) After being completely dried, the preheated adhesive is coated on the top surface of the second self-repairing layer, and then the first self-repairing layer and the second self-repairing layer are laminated and pressurized. After cooling and curing, the self-repairing composite material 1# for new energy vehicle tires is obtained.
[0099] In which, in step (1), 120# sandpaper is used for polishing, in step (2), the adhesive is preheated to 125°C, and the thickness of the adhesive layer is controlled to be 0.1 mm; the pressure is 0.4 MPa, the temperature is 130°C, and it is maintained for 8 minutes.
[0100] Example 2 Self-repairing composite material 2#
[0101] The self-repairing composite material 2# is composed of a first self-repairing layer and a second self-repairing layer connected together;
[0102] The first self-repairing layer: The first self-repairing layer is prepared by including the following ingredients, measured by weight: 80 parts of a dynamic vulcanized rubber system, 18 parts of a functional filler system and 3 parts of a vulcanization accelerator; the dynamic vulcanized rubber system includes polypropylene, natural rubber and ethylene-propylene rubber, and the amount of polypropylene added to the dynamic vulcanized rubber system is 30%; the functional filler system includes a thermally conductive filler, and the thermally conductive filler includes modified boron nitride and alumina; the vulcanization accelerator includes sulfur and N-cyclohexyl-2-benzothiazole sulfonamide.
[0103] The weight ratio of natural rubber to EPDM in the dynamic vulcanized rubber system is 2:1. The weight ratio of modified boron nitride to alumina in the thermal conductive filler is 2:1; the modified boron nitride includes silane-modified boron nitride and polymer-coated modified boron nitride, with a weight ratio of 1.5:1. The weight ratio of sulfur to N-cyclohexyl-2-benzothiazole sulfenamide in the vulcanization accelerator is 1:1.
[0104] The preparation method of the first self-repairing layer comprises the following steps:
[0105] S1: Add polypropylene, natural rubber and EPDM into an internal mixer at 155°C and mix for 10 min;
[0106] S2: Add the vulcanization accelerator, raise the temperature to 170°C, and add the functional filler system after dynamic mixing for 5 minutes;
[0107] S3: After continuing to mix for 4 minutes, the first self-repairing layer is obtained by pressing and molding through an open mill; the pressure of the open mill molding in step S3 is 10 MPa, the temperature is 160° C., and the time is 10 minutes.
[0108] Second self-repairing layer: The second self-repairing layer is prepared by including the following ingredients, measured by weight: 100 parts of thermoplastic polyurethane elastomer, 30 parts of repair microcapsules and 10 parts of modified polyimide fibers; the repair microcapsules are composed of a core material and a capsule wall, and the core material is an epoxy resin mixture or a curing agent mixture.
[0109] The repair microcapsules include Class A microcapsules and Class B microcapsules, with a weight ratio of 1.2:1; Class A microcapsules are epoxy resin microcapsules, the core materials are DGEBA epoxy resin and butylated hydroxytoluene, with a weight ratio of 60:1, and the capsule wall is polymethyl methacrylate; Class B microcapsules are curing agent microcapsules, the core materials are tetraethylenepentamine and butylated hydroxytoluene, with a weight ratio of 55:1, and the capsule wall is polyurea.
[0110] The preparation method of the second self-repairing layer comprises the following steps:
[0111] S1: Add thermoplastic polyurethane elastomer into a mixer at 110°C and mix for 8 minutes;
[0112] S2: Add the repair microcapsules and modified polyimide fibers evenly into the mixer, control the temperature at 100°C, and mix for 30 minutes;
[0113] S3: sending the uniformly mixed material into an extruder for extrusion molding, and obtaining the second self-repairing layer after cooling and molding; the extrusion molding parameters in step S3 are a temperature of 160° C. and a pressure of 8 MPa.
[0114] The method for preparing the self-repairing composite material 2# comprises the following steps:
[0115] (1) grinding the bottom surface of the first self-repairing layer and the top surface of the second self-repairing layer with sandpaper, and then cleaning them with ethanol;
[0116] (2) After being completely dried, the preheated adhesive is coated on the top surface of the second self-repairing layer, and then the first self-repairing layer and the second self-repairing layer are laminated and pressurized. After cooling and curing, the self-repairing composite material 2# for new energy vehicle tires is obtained.
[0117] In which, in step (1), 120# sandpaper is used for polishing, in step (2), the adhesive is preheated to 125°C, and the thickness of the adhesive layer is controlled to be 0.1 mm; the pressure is 0.4 MPa, the temperature is 130°C, and it is maintained for 8 minutes.
[0118] Example 3 Self-repairing composite material 3#
[0119] The self-repairing composite material 3# is composed of a first self-repairing layer and a second self-repairing layer connected together;
[0120] The first self-repairing layer: The first self-repairing layer is prepared by including the following ingredients, measured by weight: 120 parts of a dynamic vulcanized rubber system, 35 parts of a functional filler system and 8 parts of a vulcanization accelerator; the dynamic vulcanized rubber system includes polypropylene, natural rubber and ethylene-propylene rubber, and the amount of polypropylene added to the dynamic vulcanized rubber system is 15%; the functional filler system includes a thermally conductive filler, and the thermally conductive filler includes modified boron nitride and alumina; the vulcanization accelerator includes sulfur and N-cyclohexyl-2-benzothiazole sulfonamide.
[0121] The weight ratio of natural rubber to EPDM in the dynamic vulcanized rubber system is 3:1. The weight ratio of modified boron nitride to alumina in the thermal conductive filler is 3:1; the modified boron nitride includes silane-modified boron nitride and polymer-coated modified boron nitride, with a weight ratio of 2:1. The weight ratio of sulfur to N-cyclohexyl-2-benzothiazole sulfenamide in the vulcanization accelerator is 1.5:1.
[0122] The preparation method of the first self-repairing layer comprises the following steps:
[0123] S1: Add polypropylene, natural rubber and EPDM into an internal mixer at 165°C and mix for 5 minutes;
[0124] S2: Add the vulcanization accelerator, raise the temperature to 180°C, and add the functional filler system after dynamic mixing for 3 minutes;
[0125] S3: After continuing to mix for 4 minutes, the first self-repairing layer is obtained by pressing and molding through an open mixing mill;
[0126] Preferably, the pressure of the open rolling molding in step S3 is 12 MPa, the temperature is 160° C., and the time is 9 minutes.
[0127] The second self-repairing layer: The second self-repairing layer is prepared by including the following ingredients by weight: 110 parts of thermoplastic polyurethane elastomer, 40 parts of repair microcapsules and 15 parts of modified polyimide fibers; the repair microcapsules are composed of a core material and a capsule wall, and the core material is an epoxy resin mixture or a curing agent mixture.
[0128] The repair microcapsules include Class A microcapsules and Class B microcapsules, with a weight ratio of 1.4:1; Class A microcapsules are epoxy resin microcapsules, the core materials are DGEBA epoxy resin and dibutylhydroxytoluene, with a weight ratio of 70:1, and the capsule wall is polymethyl methacrylate; Class B microcapsules are curing agent microcapsules, the core materials are tetraethylenepentamine and dibutylhydroxytoluene, with a weight ratio of 65:1, and the capsule wall is polyurea.
[0129] The preparation method of the second self-repairing layer comprises the following steps:
[0130] S1: Add thermoplastic polyurethane elastomer into a mixer at 130°C and mix for 5 minutes;
[0131] S2: Add the repair microcapsules and modified polyimide fibers evenly into the mixer, control the temperature at 120°C, and mix for 20 minutes;
[0132] S3: sending the uniformly mixed material into an extruder for extrusion molding, and obtaining the second self-repairing layer after cooling and molding; the extrusion molding parameters in step S3 are a temperature of 180° C. and a pressure of 6 MPa.
[0133] The preparation method of the self-repairing composite material 3# comprises the following steps:
[0134] (1) grinding the bottom surface of the first self-repairing layer and the top surface of the second self-repairing layer with sandpaper, and then cleaning them with ethanol;
[0135] (2) After being completely dried, the preheated adhesive is coated on the top surface of the second self-repairing layer, and then the first self-repairing layer and the second self-repairing layer are laminated and pressurized. After cooling and curing, the self-repairing composite material 3# for new energy vehicle tires is obtained.
[0136] In which, in step (1), 120# sandpaper is used for polishing, in step (2), the adhesive is preheated to 125°C, and the thickness of the adhesive layer is controlled to be 0.1 mm; the pressure is 0.4 MPa, the temperature is 130°C, and it is maintained for 8 minutes.
[0137] Example 4 Self-repairing composite material 4#
[0138] The difference between Example 4 and Example 1 is that the functional filler system in Example 4 also includes a crack suppression filler and a dynamic enhancement filler; the weight ratio of the thermal conductive filler, the crack suppression filler and the dynamic enhancement filler is 8:3:3 respectively; the crack suppression filler is silane-modified nano-silicon powder, and the dynamic enhancement filler is nano-cerium oxide.
[0139] Example 5 Self-repairing composite material 5#
[0140] The difference between Example 5 and Example 1 is that Example 5 only uses silane to modify boron nitride, and does not use polymer-coated modified boron nitride.
[0141] Comparative Example 1 Comparison of Self-repairing Composite Material 1#
[0142] The difference between Comparative Example 1 and Example 1 is that the first self-repairing layer in Comparative Example 1 adopts a rubber system composed of natural rubber and ethylene-propylene rubber without dynamic vulcanization.
[0143] Comparative Example 2 Comparison of Self-repairing Composite Material 2#
[0144] The difference between Comparative Example 2 and Example 1 is that the amount of polypropylene added in Comparative Example 2 is 45%.
[0145] Comparative Example 3 Comparison of Self-repairing Composite Material 3#
[0146] The difference between Comparative Example 3 and Example 1 is that the thermal conductive filler in Comparative Example 3 uses unmodified boron nitride and aluminum oxide.
[0147] Comparative Example 4 Comparative Self-repairing Composite Material 4#
[0148] The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, modified polyimide fiber is not used in the second self-repairing layer.
[0149] Experimental example
[0150] The self-repairing composite materials prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to the following experimental tests:
[0151] 1. Thermal stability test: Tested in accordance with ISO 188:2011 standard, after high temperature aging, compare the initial mass and the mass after aging of the sample, and calculate the mass loss rate. The lower the mass loss rate, the better the thermal stability of the sample, mass loss rate = ((initial mass - final mass) / initial mass) × 100%.
[0152] 2. Dynamic compression fatigue resistance test
[0153] Reference standard: ASTM D575 (Rubber compression performance test)
[0154] Purpose: To determine the fatigue properties of composite materials under dynamic compression.
[0155] Method: Sample size: 10mm×10mm×10mm; apply cyclic compressive stress (frequency 5Hz, maximum strain 30%). Record the final failure cycle of the sample. To be closer to the actual situation, count 10 times and round up to the nearest integer for statistics. The greater the number, the better the fatigue resistance.
[0156] 3. Impact resistance test
[0157] Refer to GB / T 1043-2008 (Simply supported beam impact test) and record the impact strength.
[0158] 4.Fix performance test
[0159] The self-repairing composite materials prepared in Examples 1-5 and Comparative Examples 1-4 were added into corresponding tires prepared according to conventional tire manufacturing processes, and the repairing ability was tested.
[0160] The experimental conditions are as follows:
[0161] a. Tire pretreatment: The self-repairing layers made of the composite materials of the embodiment and the comparative example were applied to the interlayer of the tires of the same model, and the initial inflation pressure (2.5 bar) was recorded using a pressure sensor.
[0162] b. Leakage simulation: Use a plum blossom awl to create two holes of different diameters and shapes at different locations on the tire surface [approximately 2.0 mm and 3.0 mm (with cracks on the edges)]. Mark the edge area of each damaged area to facilitate subsequent observation and data recording.
[0163] c. Patching process test:
[0164] An equivalent load (300 kg) was applied to a single wheel on a tire testing machine. The drum speed simulated the speed of driving at a speed of 80 km / h. The internal pressure of the tire was recorded after 30 minutes.
[0165] d. Data Recording:
[0166] Repair efficiency = pressure value after repair / initial pressure value × 100%, rounded off.
[0167] The test results of each experiment are shown in Table 1.
[0168] Table 1 Performance tests of self-repairing composite materials prepared in Examples 1-5 and Comparative Examples 1-4
[0169]
[0170] From the above results, it can be seen that the self-repairing composite materials prepared by the components and methods defined in the present application have excellent heat resistance, fatigue resistance, impact resistance and repair ability. The mass loss rates of Examples 1-4 are all less than 1%, the final number of failures in dynamic fatigue tests is high, the impact strength is all above 60J, and the repair efficiency is all above 90%, indicating that the repair effect on different types of irregular damage or cracks is good and the comprehensive performance is excellent.
[0171] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0172] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A self-repairing composite material for new energy vehicle tires, characterized in that: It is composed of a first self-repairing layer and a second self-repairing layer connected together; The first self-repairing layer is prepared by the following ingredients, measured by weight: 80-120 parts of a dynamic vulcanized rubber system, 18-35 parts of a functional filler system, and 3-8 parts of a vulcanization accelerator; the dynamic vulcanized rubber system includes polypropylene, natural rubber, and ethylene-propylene rubber, and the amount of polypropylene added to the dynamic vulcanized rubber system does not exceed 30%; the functional filler system includes a thermally conductive filler, and the thermally conductive filler includes modified boron nitride and aluminum oxide; the vulcanization accelerator includes sulfur and N-cyclohexyl-2-benzothiazole sulfenamide; The second self-repairing layer is prepared by the following ingredients, measured by weight: 100-110 parts of thermoplastic polyurethane elastomer, 30-40 parts of repair microcapsules and 10-15 parts of modified polyimide fibers; the repair microcapsules are composed of a core material and a capsule wall, and the core material is an epoxy resin mixture or a curing agent mixture.
2. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The weight ratio of natural rubber to ethylene-propylene rubber in the dynamically vulcanized rubber system is (2-3):
1.
3. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The weight ratio of modified boron nitride and aluminum oxide in the thermal conductive filler is (2-3):1; The modified boron nitride comprises silane-modified boron nitride and polymer-coated modified boron nitride, and the weight ratio is (1.5-2):
1.
4. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The functional filler system also includes crack suppression fillers and dynamic enhancement fillers; The weight ratio of the thermal conductive filler, crack suppression filler and dynamic reinforcement filler is (6-12): (3-7): (2-5); Preferably, the crack suppression filler is silane-modified nano-silicon powder, and the dynamic enhancement filler is nano-cerium oxide.
5. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The weight ratio of sulfur to N-cyclohexyl-2-benzothiazole sulfenamide in the vulcanization accelerator is (1-1.5):
1.
6. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The preparation method of the first self-repairing layer comprises the following steps: S1: Add polypropylene, natural rubber and EPDM into an internal mixer at a temperature of 155-165°C and mix for 5-10 minutes; S2: Add the vulcanization accelerator, raise the temperature to 170-180°C, dynamically mix for 3-5 minutes, and then add the functional filler system; S3: After continuing to mix for 2-4 minutes, the first self-repairing layer is obtained by pressing and molding through an open mixer; Preferably, the pressure of the open rolling molding in step S3 is 10-12 MPa, the temperature is 160-165° C., and the time is 8-10 min.
7. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The repair microcapsules include type A microcapsules and type B microcapsules, with a weight ratio of (1.2-1.4):1; The type A microcapsule is an epoxy resin microcapsule, the core material is DGEBA epoxy resin and dibutyl hydroxytoluene, the weight ratio is (60-70):1, and the capsule wall is polymethyl methacrylate; The B-type microcapsule is a curing agent microcapsule, the core material is tetraethylenepentamine and dibutylhydroxytoluene, the weight ratio is (55-65):1, and the capsule wall is polyurea.
8. The self-repairing composite material for new energy vehicle tires according to claim 1, characterized in that: The preparation method of the second self-repairing layer comprises the following steps: S1: Add thermoplastic polyurethane elastomer into a mixer at a temperature of 110-130°C and mix for 5-8 minutes; S2: Add the repair microcapsules and modified polyimide fibers evenly into the mixer, control the temperature at 100-120°C, and mix for 20-30 minutes; S3: sending the uniformly mixed material into an extruder for extrusion molding, and obtaining the second self-repairing layer after cooling and molding; Preferably, the extrusion molding parameters in step S3 are a temperature of 160-180° C. and a pressure of 6-8 MPa.
9. A method for preparing a self-repairing composite material for new energy vehicle tires as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) grinding the bottom surface of the first self-repairing layer and the top surface of the second self-repairing layer with sandpaper, and then cleaning them with ethanol; (2) After being completely dried, the preheated adhesive is coated on the top surface of the second self-repairing layer, and then the first self-repairing layer and the second self-repairing layer are laminated and pressurized. After cooling and curing, the self-repairing composite material for new energy vehicle tires is obtained.
10. A tire, comprising, from outside to inside, a tread layer, a self-repairing composite material layer and an inner tire layer, characterized in that: The self-repairing composite material layer is a self-repairing composite material for new energy vehicle tires as described in any one of claims 1 to 8 or a self-repairing composite material for new energy vehicle tires prepared by the preparation method of claim 9, wherein the first self-repairing layer is arranged close to the tread layer, and the second self-repairing layer is arranged close to the tire inner layer.
Citation Information
Patent Citations
Sealant for self-repairing tire, preparation method of sealant, and self-repairing tire
CN114058293A
Tyre of which the tread comprises a thermoplastic vulcanizate (TPV) elastomer
CN102906178A
Three-proofing composite tire with puncture-proof, explosion-proof and bulletproof functions
CN116353257A
Disc-covering type self-repairing sealing material for preventing new energy automobile tire from being punctured and preparation method of disc-covering type self-repairing sealing material
CN116396605A
Modified polyimide short fiber / thermoplastic polyurethane composite material and preparation method thereof
CN117106295A
Cited By
Anti-stray current solvent-free insulating elastic coating for track and preparation method of anti-stray current solvent-free insulating elastic coating
CN122213832A